2019
DOI: 10.1016/j.devcel.2018.11.035
|View full text |Cite
|
Sign up to set email alerts
|

SPOP Promotes Nanog Destruction to Suppress Stem Cell Traits and Prostate Cancer Progression

Abstract: SUMMARY Frequent SPOP mutation defines the molecular feature underlying one of seven sub-types of human prostate cancer (PrCa). However, it remains largely elusive how SPOP functions as a tumor suppressor in PrCa. Here, we report that SPOP suppresses stem cell traits of both embryonic stem cells and PrCa cells through promoting Nanog poly-ubiquitination and subsequent degradation. Mechanistically, Nanog, but not other pluripotency-determining factors including Oct4, Sox2, and Klf4, specifically interacts with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 68 publications
2
50
0
Order By: Relevance
“…4a). 282,283 As ubiquitination is a reversible process, Nanog may also be regulated by deubiquitinating enzymes during stem cell or somatic cell reprogramming. To screen the DUB of Nanog, the deubiquitinating enzyme USP21 was identified by the efficient dual-luciferase reporter assay system.…”
Section: Nanog Ubiquitinationmentioning
confidence: 99%
“…4a). 282,283 As ubiquitination is a reversible process, Nanog may also be regulated by deubiquitinating enzymes during stem cell or somatic cell reprogramming. To screen the DUB of Nanog, the deubiquitinating enzyme USP21 was identified by the efficient dual-luciferase reporter assay system.…”
Section: Nanog Ubiquitinationmentioning
confidence: 99%
“…Importantly, KPT-6566 treatments caused selective killing of malignant cells and also suppressed the CSC-like phenotype in vitro and metastasis growth in the lungs [201]. Another small molecule inhibitor of PIN1, PiB, inhibited both SPOP-mediated NANOG degradation and stemness-associated spheroid formation in prostate cancer cells [197]; the application of PIN1 inhibitors against prostate cancer with wild-type SPOP was suggested by the researchers. As for pharmaceutical targeting, all-trans retinoic acid-mediated inhibition of PIN1 was shown to eliminate gastric CSCs and also impair their self-renewal and tumorigenic potential [189].…”
Section: Targeting Peptidyl-prolyl Isomerases and Use Of Fkbpl-derivementioning
confidence: 99%
“…In fact, PIN1 overexpression may be an essential cause for the tumorigenesis and cancer stemness development in breast and pancreatic carcinomas [186,195,196]. Studies of the roles of SPOP and PIN1 in prostate cancer stemness and progression have revealed that PIN1 is an upstream regulator of NANOG and also protects the latter from SPOP-mediated polyubiquitination and degradation, thus promoting NANOG-conferred cancer stemness features in prostate tumors [197].…”
Section: Immunophilins and Immunophilin-like Peptidyl-prolyl Isomerasesmentioning
confidence: 99%
“…As an adaptor of Cul3-based ubiquitin ligase, SPOP is ubiquitously expressed, although in varied quantities, in different tissues [31]. It affects many biological processes by binding and triggering the ubiquitination and proteasomal degradation of target proteins [21,32]. Previous research indicates that SPOP binds with MyD88 and promotes the degradation [23].…”
Section: Discussionmentioning
confidence: 99%